2017
DOI: 10.1111/jvs.12592
|View full text |Cite
|
Sign up to set email alerts
|

New insights into plants co‐existence in species‐rich communities: The pollination interaction perspective

Abstract: Questions: In animal-mediated pollination, pollinators can be regarded as a limiting resource for which entomophilous plant species might interact to assure pollination, an event pivotal for their reproduction and population maintenance. At community level, spatially aggregated co-flowering species can thus be expected to exhibit suitable suites of traits to avoid competition and ensure pollination. We explored the problem by answering the following questions: (i) are co-flowering species specialized on differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 91 publications
(114 reference statements)
2
35
0
Order By: Relevance
“…Desaegher et al (2018) showed that floral visitors of insect families that had a preference for nontubular corollas (generally insects with small mouthparts and considered as specialists) were rare in urbanized areas of the Île-de-France region (see also Geslin, Gauzens, Thébault, & Dajoz, 2013). In different contexts, two recent community-level studies (Bergamo, Wolowski, Maruyama, Vizentin-Bugoni, & Sazima, 2018;Fantinato, Del Vecchio, Giovanetti, Acosta, & Buffa, 2018) suggested complex interplay of facilitation and competition processes among flowering plants through pollination by insects. In different contexts, two recent community-level studies (Bergamo, Wolowski, Maruyama, Vizentin-Bugoni, & Sazima, 2018;Fantinato, Del Vecchio, Giovanetti, Acosta, & Buffa, 2018) suggested complex interplay of facilitation and competition processes among flowering plants through pollination by insects.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Desaegher et al (2018) showed that floral visitors of insect families that had a preference for nontubular corollas (generally insects with small mouthparts and considered as specialists) were rare in urbanized areas of the Île-de-France region (see also Geslin, Gauzens, Thébault, & Dajoz, 2013). In different contexts, two recent community-level studies (Bergamo, Wolowski, Maruyama, Vizentin-Bugoni, & Sazima, 2018;Fantinato, Del Vecchio, Giovanetti, Acosta, & Buffa, 2018) suggested complex interplay of facilitation and competition processes among flowering plants through pollination by insects. In different contexts, two recent community-level studies (Bergamo, Wolowski, Maruyama, Vizentin-Bugoni, & Sazima, 2018;Fantinato, Del Vecchio, Giovanetti, Acosta, & Buffa, 2018) suggested complex interplay of facilitation and competition processes among flowering plants through pollination by insects.…”
Section: Introductionmentioning
confidence: 99%
“…In different contexts, two recent community-level studies (Bergamo, Wolowski, Maruyama, Vizentin-Bugoni, & Sazima, 2018;Fantinato, Del Vecchio, Giovanetti, Acosta, & Buffa, 2018) suggested complex interplay of facilitation and competition processes among flowering plants through pollination by insects. This differentiation may allow different pollen placement on pollinator bodies, which can reduce competition among plant species and increase effective pollination (Bergamo et al, 2018;Fantinato et al, 2018). These studies also showed that coflowering, pollinator-sharing species tended to differ in another position in the corollas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the regional scale, reproductive processes involving pollination and seed dispersal are crucial because the production of seeds is necessary for the colonization of new sites (Escaravage & Wagner, ). Furthermore, in some plant communities, they also contribute to shaping patterns of species co‐occurrence at smaller scales (Fantinato, Del Vecchio, Giovanetti, Acosta, & Buffa, ; Heystek & Pauw, ). Processes linked to vegetative reproduction and growth in plant communities influence species co‐occurrence at a small spatial scale through interactions as competition for light, space and below‐ground resources (Kelemen et al., ; van der Maarel & Sykes, ).…”
Section: Introductionmentioning
confidence: 99%